2015
DOI: 10.1164/rccm.201408-1468oc
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Automated Microscopy for Microbiological Surveillance of Ventilator-associated Pneumonia

Abstract: Rationale: Diagnosis of ventilator-associated pneumonia (VAP) is imprecise.Objectives: To (1) determine whether alternate-day surveillance mini-bronchoalveolar lavage (mini-BAL) in ventilated adults could reduce time to initiation of targeted treatment and (2) evaluate the potential for automated microscopy to reduce analysis time.Methods: Adult intensive care unit patients who were anticipated to require ventilation for at least a further 48 hours were included. Mini-BALs were processed for identification, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…The assay has been demonstrated to be successful at both pathogen identification and antimicrobial susceptibility assessment from blood culture 101 . Further preliminary tests indicate that this system is capable of direct detection of pathogens from patient blood, urine, and sputum samples 100,102,103 . The phenotypic measures used for pathogen identification are not precise, but the system is also amenable to process samples for species identification methods such as FISH.…”
Section: Real-time Microscopy Systems For Astmentioning
confidence: 98%
“…The assay has been demonstrated to be successful at both pathogen identification and antimicrobial susceptibility assessment from blood culture 101 . Further preliminary tests indicate that this system is capable of direct detection of pathogens from patient blood, urine, and sputum samples 100,102,103 . The phenotypic measures used for pathogen identification are not precise, but the system is also amenable to process samples for species identification methods such as FISH.…”
Section: Real-time Microscopy Systems For Astmentioning
confidence: 98%
“…Inaccurate diagnosis or inappropriate antimicrobial therapy, including the treatment of tracheobronchial colonisation, should be avoided. In time, newer technology may allow us to diagnose VAT and VAP in more sophisticated ways (Douglas IS, 2015;Bos LD, 2014), and determine which patients may be at an increased risk of progression from VAT to VAP based on immunological factors. This may enable targeted therapy towards those patients with VAT at the greatest risk of progression to VAP, with improved survival and a minimal excess use of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Douglas et al reported the use of this technology as a microbiological surveillance method for VAP in ICU patients (31). This study used 73 samples collected from 33 patients, with a reported sensitivity of 100% (7/7) and specificity of 97% (64/66) compared to conventional microbiological culture.…”
Section: Automated Microscopy As a Poct Tool For Vapmentioning
confidence: 99%